Pengaruh Sistem Pengendalian Internal Terhadap Pencegahan Kecurangan (Fraud) Dalam Pengelolaan Dana Desa Dengan Moralitas Sebagai Variabel Moderasi : (Studi Empiris Pada Desa-desa di Kecamatan Saparua) - Julio Noya; Revi Wilhelmina Silooy; Franco Benony Limba (Universitas 45 Surabaya, 2023)
This study aims to empirically examine the effect of the internal control system on the prevention of fraud (fraud) in managing village funds with morality as a moderating variable. The population of this study were all village apparatus in 7 village offices in Saparua sub-district. The sampling technique in this study was purposive sampling in order to obtain 58 samples. Respondents in this study were the village head, secretary, treasurer and employee in charge of managing village finances. Data analysis to test the hypothesis using SmartPLS Version 3.2.9 for windows. The results showed that: The Internal Control System has a significant effect on fraud prevention and Morality is able to moderate the internal control system on fraud prevention.